Pengaruh Penggunaan Abu Batang Pisang Dan Abu Cangkang Sawit Ditambah Sikacim Concrete Additive Terhadap Kuat Tekan Beton - Alloto'dang, Hizkia Rial; Sariman, Syahrul; Setiawan, Arman (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Research on increasing the compressive strength of concrete by using various types of additives has been widely carried out, so this research also uses additives, namely the use of banana stem ash and palm shell ash, which aims to determine the comparison of the two additives, as well as the effect of adding concrete. Contains Sikacim Concrete Additive. Variations in banana stem ash and palm shell ash (4%, 5% and 6%) of the cement weight as well as the addition of Sikacim Concrete Additive as much as 0.6% of the cement weight. The average compressive strength of the concrete samples was measured and compared. The research results showed that the higher the percentage of banana stem ash and palm shell ash used, the higher the compressive strength of the concrete produced. The compressive strength of variations in banana stem ash is greater than variations in palm shell ash with percentages of 14.13%, 11.17% and 7.08. The effect of adding sikacim concrete on banana stem ash was 3.17%, 1.39%, 6.73 and on palm shell ash was 2.88%, 4.32%, 3.99% compared to before adding sikacim. Banana stem ash at a percentage of 6% with the addition of sikacim had the highest increase with a compressive strength of 29.91 Mpa.